Integration of academic and health education for the prevention of physical aggression and violence in young people: systematic review, narrative synthesis and intervention components analysis. Issue 9 (21st September 2018) - Melendez-Torres, G.J.; Tancred, Tara; Fletcher, Adam; Campbell, Rona; Thomas, James; Bonell, Christopher
Abstract : Objectives: To systematically review evidence on the effectiveness of interventions including integration of academic and health education for reducing physical aggression and violence, and describe the content of these interventions. Data sources: Between November and December 2015, we searched 19 databases and 32 websites and consulted key experts in the field. We updated our search in February 2018. Eligibility criteria: We included randomised trials of school-based interventions integrating academic and health education in students aged 4–18 and not targeted at health-related subpopulations (eg, learning or developmental difficulties). We included evaluations reporting a measure of interpersonal violence or aggression. Data extraction and analysis: Data were extracted independently in duplicate, interventions were analysed to understand similarities and differences and outcomes were narratively synthesised by key stage (KS). Results: We included 13 evaluations of 10 interventions reported in 20 papers. Interventions included either full or partial integration, incorporated a variety of domains beyond the classroom, and used literature, local development or linking of study skills and health promoting skills. Evidence was concentrated in KS2, with few evaluations in KS3 or KS4, and evaluations had few consistent effects; evaluations in KS3 and KS4 did not suggest effectiveness. Discussion: Integration of academic and health education may be a promising approach, but more evidence is needed. Future research should consider the 'lifecourse' aspects of these interventions; that is, do they have a longitudinal effect? Evaluations did not shed light on the value of different approaches to integration.